"Bring in your parents day": building inclusion and engagement through a cross-generational family-friendly workplace initiative. Issue 1 (27th November 2019) - Beauregard, T. Alexandra; King, Karin A.
Abstract : Purpose: Employer-sponsored family-friendly events are designed to boost engagement and encourage retention by building family members' identification with the organization. These events are usually targeted at employees with dependent children, but LinkedIn's more inclusive "Bring in Your Parents" (BIYP) initiative aims to introduce employees' parents to the daily work of their adult children. This study evaluates the impact of BIYP on the attitudes and behavioral intentions of participating employees and their parents. Design/methodology/approach: Repeated-measures surveys were conducted among participating employees and parents in six organizations in six countries (UK, Ireland, France, Brazil, Mexico and Colombia). These were followed by in-person interviews with participating employees (UK) and phone interviews with HR managers (Brazil, Canada, France, Spain, UK and USA). Findings: Participation in BIYP increases employee engagement and parents' instrumental and affective support for their children and for their children's employers. Hosting BIYP is perceived to enhance corporate reputation among both internal and external stakeholders. Practical implications: BIYP serves the dual function of building employee engagement and creating new parental brand ambassadors for participating organizations. BIYP can be an effective tool for employers to engage members of staff not traditionally included in organizational family-friendly events and may be particularly useful for firms with a high proportion of younger workers in tech-savvy jobs. Originality/value: This evaluation of a new workplace initiative demonstrates measurable effects on important employee attitudes and behavioral intentions.